Esophageal exclusion and bypass for corrosive injury: The lessons learnt - Richa Lal; Anu Behari; Jayanth Reddy; Banani Poddar (Wolters Kluwer Medknow Publications, 2014)
While it is always preferable to excise and replace the diseased esophagus in corrosive injuries, the surgeon may be compelled to exclude and bypass it by a substernal conduit in select situations wherein excision is technically hazardous. This case illustrates the lessons learnt from a potentially life-threatening complication of bipolar esophageal exclusion.